New Ways of Working (NWOW) and Work Engagement: The Mediating Roles of Proactive Personality and Job Crafting - Cheryl Dhewina, Wong (Universiti Malaysia Sarawak, 2025)
Despite increasing research on work engagement, more empirical studies are needed to enhance our understanding in this area pertaining to specific contextual and cultural setting. Organizations recognize that work engagement is crucial for talent retention, especially when New Ways of Working (NWOW) were implemented and created uncertainty. Employees with a proactive personality, who take initiative and pursue goals, play a key role in navigating these changes. Additionally, job crafting, which is shaping job resources and demands, also fosters engagement. Therefore, this study integrates proactive personality and job crafting as mediators to study the relationship between NWOW and work engagement. A total of 158 respondents in the Real Estate (REI) and Architecture, Engineering, and Construction (AEC) industries participated via an online questionnaire. The data were analyzed using Spearman's correlation and Hayes's PROCESS Macro in SPSS Version 23. The correlation analysis revealed significant relationship between NWOW and work engagement. The PROCESS Macro analysis showed that proactive personality and job crafting partially mediate this relationship. These results have important implications for literature on work engagement, human resource development (HRD) and the REI and AEC industry. It is suggested that organizations should promote proactive traits and job crafting behaviors through training while creating environments that encourage autonomy and innovation.